Professionalization trajectory of healthcare interpreter certification in the context of the language industry: a comparative study of industry-led and government-led models, with implications for China - Hu, Wei; Jiang, Jiaming (Frontiers in Public Health, 2025)
This study investigates the professionalization trajectory of healthcare interpreter certification under the emerging paradigm of the language industry and discusses the implications for China's nascent system. Against the backdrop of increasing linguistic diversity and growing demands for multilingual healthcare communication, two contrasting institutional models are compared: the industry-led model favored in the United States and the government-led model as developed in Japan. Drawing on professionalization theory and the political economy of language services, the paper explores how different actors—professional associations, state agencies, and language service providers—shape certification standards, ethical frameworks, and service integration mechanisms. The analysis highlights the differences between the two model types: while the U.S. model prioritizes decentralized standard-setting, market-driven legitimacy, and platform-based coordination, the Japanese model relies on centralized policy engineering, institutionalized ethics, and government-led service embedding. Building on this comparative framework, the paper proposes a dual-track approach to certification system development in China, combining top-down policy guidance with bottom-up industry collaboration. While this model offers a balanced pathway toward standardization and flexibility, it also entails potential risks such as institutional overlaps, uneven regional adoption, and challenges of long-term sustainability. It argues that healthcare interpreter certification should function not only as a regulatory mechanism but also as a strategic instrument for language governance, public health equity, and industry development. The study concludes by advocating for the integration of certification systems into China's national language strategy, emphasizing institutional sustainability, ethical accountability, and international competitiveness as key pillars of a future-oriented healthcare language service ecosystem.